2016
DOI: 10.5339/nmejre.2016.1
|View full text |Cite
|
Sign up to set email alerts
|

The crisis of research and global recognition in Arab universities

Abstract: Scientific research is facing a critical situation in Arab nations. While international rankings have become the first priority of universities engaged in research across the world, most universities undertaking scientific research in the Arab region are occupied with other matters more vital to their survival. Given the current crisis in some universities in the Arab region, this study seeks to understand the factors responsible for the falling standards in scientific research and the lack of global recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…pouring oil revenues into technology and science research, [14][15][16] which was markedly illustrated on February 9th, 2021, when the United Arab Emirates became the rst Arab country and the fth country worldwide to send a probe to Mars. [17] De cient funding can impede the establishment of robust research infrastructures within Arab medical schools and medical centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pouring oil revenues into technology and science research, [14][15][16] which was markedly illustrated on February 9th, 2021, when the United Arab Emirates became the rst Arab country and the fth country worldwide to send a probe to Mars. [17] De cient funding can impede the establishment of robust research infrastructures within Arab medical schools and medical centers.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, most Arab medical schools and hospitals remain patient-centered and clinically-oriented, as only recently has a research culture been prioritized. [15,18] Furthermore, wars, internal turmoil, and ongoing con icts may further jeopardize research activity in the Arab world by channeling funds usually allocated for biomedical research activity towards military action and into ful lling basic needs. War-torn countries also suffer from brain drain and insecure environments that can hamper research activity.…”
Section: Discussionmentioning
confidence: 99%
“… 9 10 Lack of advanced research infrastructure and deficient funding further widen the gap between the Arab world and the Western countries. 11 12 Countries like Yemen, Mauritania, Somalia, Djibouti and Comoros suffer from widespread poverty. In addition, these countries fare poorly with regard to security, health, education and proper nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a review of educational research papers published in international journals between 1995 and 2006 found that only 36 articles were related to the Arab region, representing only 1.7% of the total number of papers (2,112) published (El-Zeki, 2008). While we acknowledge the limitation of using international publication counts as the only measure of contribution to international knowledge, the low productivity of Arab countries in terms of wider indicators of scientific knowledge is well documented (see Abouchedid and Abdelnour, 2015;Almansour, 2016;Hanafi and Arvanitis, 2015). Hanafi and Arvanitis (2015) observe that several political, institutional, cultural and financial barriers have long hampered these countries' efforts to transform into 'knowledge societies'.…”
Section: Knowledge Production In Oman and Ethiopia: Understanding The Contextmentioning
confidence: 99%